Displaying Dissent: On Faith, Consumerism, and Censorial Discipline in the Israeli Museum - Nissim Gal; Ronit Milano (Athens Journal of Humanities & Arts, 2022)
An unusual violent clash between religious, Christian and Muslim demonstrators and the Haifa Museum of Art took place on Thursday, January 9, 2019. The protesters amassed the entrance of the museum to express their distress against the exhibition Shop It! A handheld firebomb thrown towards the museum was but the first round for the violent reactions of the next several days. These included attacking police forces and attempts to break into the museum featuring works of art considered sacrilegious by the demonstrators. The protest developed into a multi-participant debate in the art scene, involving ordinary citizens, artists and art curators, local church leaders, the city mayor, the minister of culture and other politicians, civil rights organizations and the court, as each part sought to exercise civic, moral, ethical or practical authority to censor the position or the work of the other. The article seeks to analyze the different ways in which mechanisms of regularization, supervision and punishment, which have always been part of the world of art, are used not only by those perceived as apparatuses of the state or as ideological mechanisms of abstract political or institutional entity, but as standard practices in the discourse of creating, trading, curating and presenting art – a discourse which, in the Israeli-Palestinian context, is imbued with the notion of national conflict.